Aortic stiffness, living donors, and renal transplantation - Bahous, Sola Aoun (2006)
In subjects with renal disease, reduced renal function and increased arterial stiffness are significantly associated in cross-sectional studies. The relationship is independent of age, blood pressure (BP), and atherosclerosis. Because both variables are independent predictors of cardiovascular risk, time-dependent relationships between them are important to determine. Aortic pulse wave velocity was measured noninvasively by comparison with healthy volunteers in 101 living kidney donors and their 101 corresponding recipients. Healthy volunteers were divided into 2 groups: one was recipient related through familial links and the other was nonrecipient related. Independently of age, gender, and BP, pulse wave velocity was significantly elevated in donors and recipients by comparison with the 2 groups of healthy volunteers. Pulse wave velocity was significantly higher in the recipient-related than in the nonrecipient-related group. Whereas in healthy volunteers, pulse wave velocity was exclusively related to age, gender, and BP, in donors and recipients, it was rather associated with a cluster of cardiovascular risk factors, including smoking habits and plasma glucose. Major factors related to pulse wave velocity were renal: time since nephrectomy (donation date) in donors, in whom pulse pressure was specifically associated with proteinuria, and renal rejection in recipients. Plasma creatinine doubling secondary to chronic allograft nephropathy was significantly associated with renal rejection and donor pulse wave velocity, independent of age. Our findings strongly suggest consistent interactions (including familial factors) between kidney function and arterial stiffness. Assessment of cause–effect relationships and implication of biochemical and/or genetic factors warrant additional studies.